The Experience of Pediatric Palliative Caregiving: A Qualitative Analysis From the Photographs of Meaning Program. (May 2020) - Levy, Kathryn; Grant, Pei C.; Tenzek, Kelly E.; Depner, Rachel M.; Pailler, Megan E.; Beaupin, Lynda K.
The Photographs of Meaning Program for pediatric palliative caregivers (POM-PPCG) is an innovative, meaning-based intervention utilizing photovoice and social media components. In 2017, 9 pediatric palliative caregivers participated in this intervention. During the social media portion of the POM-PPCG, participants were presented with weekly themes based on a meaning-making curriculum. In response, they took photographs, applied either audio or typed narratives, and shared them via social media. Ninety-five photographs with narratives were produced during the intervention. Through thematic qualitative analysis with consensual qualitative research components, 5 themes were identified: Love, Challenges, Loss, Coping, and The New Normal . This study adds to existing literature by shedding light on the experiences of caregivers of children with palliative care needs. Findings from this research contribute not only to the innovative use of qualitative methods but also to the clinical knowledge and practice regarding the pediatric palliative caregiver experience.